Media Pembelajaran Berbasis STEM Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa - Aprianti, Yesi Dian; Ayu, Hena Dian; Sundaygara, Chandra (RAINSTEK: Jurnal Terapan Sains dan Teknologi, 2023)
The aim of this research is to produce STEM-based learning media in the form of learning videos that have been tested for feasibility , practicality and effectiveness to improve students' critical thinking. The research model used is ADDIE, namely: 1) initial needs analysis to determine student needs; 2) initial media design and creating research instruments; 3) video development using the Canva and Animeker applications , as well as validation by media, material and language experts; 4) small-scale limited trials on 30 class VIII students; 5) evaluation from users, namely students and subject teachers. The results of media, material and language expert data analysis state that STEM-based learning media is suitable for use. Based on the feasibility assessment from media experts, a score of 93.75% was obtained, material experts obtained a score of 82% and language experts obtained a score of 90% in the "very valid" category. The results of the small-scale test assessment on 30 students obtained a score of 0.56, which is included in the "medium" category. So it can be concluded that STEM-based learning media on rectilinear motion material is suitable for use by students as learning media to improve students' critical thinking skills. The results of this research show that the use of STEM-based learning media in the form of learning videos can improve students' critical thinking skills, because videos can present information in the form of text, images, sound and can clarify abstract concepts. Keywords: Video Learning Media, Straight Movement, Critical Thinking Ability